Impact of Age on Ovarian Response and IVF Outcome during Controlled Ovarian Hyperstimulation in Women from Gaza Strip (Journal of Medicine, 2014)
Background: Although age is an important factor in female fertility, not much date were focused on the relationship between age and ovarian response and in vitro fertilization (IVF) outcome. However, the female reproductive capacity varies with age.Objective: To assess the impact of age on ovarian response and IVF outcome during controlled ovarian hyperstimulation in women from Gaza Strip. Methods: This prospective cohort study consisted of 75 women attending IVF at Al-Basma Fertility Center in Gaza City. The number of oocytes and embryos were recorded for each female and the occurrence of pregnancy was followed for three months. The obtained data were computer analyzed using SPSS statistical package version 18.Results: The mean age of the study population was 29.2±5.9 years. The total number of oocytes was significantly decreased with increasing age (F=3.932 and P=0.024).In this context Pearson correlation test exhibited negative significant correlation between women age and the number of mature oocyte (r=-0.276, P=0.017). There was an inverse relationship between age and ovarian response (F=6.773 and P=0.001), showing good response (9-16 oocytes) at mean age of 26.7±5.0 years. When related to women age, IVF outcome showed that the chance of getting pregnant increased with decreased age (F=4.278 and p= 0.018). Conclusion: The ovarian response and the chance of getting pregnancy were diminishing with ageing, implying that maternal age should by consider during IVF program.DOI: http://dx.doi.org/10.3329/jom.v15i1.19858 J Medicine 2014; 15: 36-40